2021
DOI: 10.1039/d1gc00353d
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of a jet fuel range dicycloalkane by the aqueous phase hydrodeoxygenation of polycarbonate

Abstract: For the first time, propane-2,2-diyldicyclohexane, a jet fuel range C15 dicycloalkane was directly produced by the aqueous-phase hydrodeoxygenation (APHDO) of polycarbonate (PC). Among the investigated catalyst systems, a mixture of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…[37] The isopropanol served as both the solvent and hydrogen donor. Meanwhile, a one-step route to convert PC into a jet fuel range dicycloalkane with very high yields was achieved by the same group using the catalysts of Rh/C and H-USY by the aqueous phase HDO at 200°C under 35 bar H 2 after 12 h. [38] Rorrer et al employed n-octadecane as a model compound and screened several metal-based catalysts for the hydrogenolysis. [39] The Ru/C catalyst displayed the most outstanding performances, which almost quantitatively converted the model compound into gaseous and liquid alkanes at 200°C and into predominantly CH 4 at 250°C.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…[37] The isopropanol served as both the solvent and hydrogen donor. Meanwhile, a one-step route to convert PC into a jet fuel range dicycloalkane with very high yields was achieved by the same group using the catalysts of Rh/C and H-USY by the aqueous phase HDO at 200°C under 35 bar H 2 after 12 h. [38] Rorrer et al employed n-octadecane as a model compound and screened several metal-based catalysts for the hydrogenolysis. [39] The Ru/C catalyst displayed the most outstanding performances, which almost quantitatively converted the model compound into gaseous and liquid alkanes at 200°C and into predominantly CH 4 at 250°C.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…It has been reported that the two reactions can be conducted sequentially or in one-pot, depending on the solvents and catalysts that were applied in the system (Figure 10). [63][64][65] For instance, in a two-step process, PC underwent alcoholysis with methanol generated bisphenol A in a yield up to 90 % in the absence of any catalyst at 453 K. Then a dual catalyst composed of Pt/C and H-β catalyzed the subsequent hydrodeoxygenation of bisphenol A in 3 MPa H 2 at 413 K, affording jet fuel-range C 15 cycloalkanes with a high yield of 87 %. [63] The excellent performance of this dual catalyst is contributed to high activity of Pt/C for hydrogenation of the benzene ring in bisphenol A, and the relatively high pore size and acidity of H-β (compared to other zeolites such as HZSM-5 and MOR), which favored intermediates diffusion and promoted dehydration of hydroxy groups.…”
Section: Catalytic Conversion Of Plastics With Aromatic Monomers To J...mentioning
confidence: 99%
“…Recently, a combination catalyst of commercial Rh/C and H-USY has been explored for the one-pot transformation of PC. [64] The yield of jet fuel-range C 15 cycloalkane (i. e., propane-2,2-diyldicyclohexane) reached as high as 94.9 % after reaction of PC at 473 K and 3.5 MPa H 2 . When chopped DVD disk (a representative of real PC waste) was subject to such catalytic system, a high yield of 86.9 % was obtained under the same reaction conditions.…”
Section: Catalytic Conversion Of Plastics With Aromatic Monomers To J...mentioning
confidence: 99%
See 1 more Smart Citation
“…Step Characterization. One-dimensional (1D) ( 1 H, 13 C NMR) and two-dimensional (2D) ( 1 H-1 H COSY, 1 H-13 C-HSQC) NMR was performed using Varian Inova (600 MHz in DMSO-d 6 as the internal standard). The instruments and methods used for thermal-mechanical property evaluation are the same as those in our previous work.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%